Social capital and educational aspiration of students: does family social capital affect more compared to school social capital? - Shahidul, S. M.; Karim, A.H.M Zehadul; Mustari, S. (Canadian Center of Science and Education, 2015)
Resources from multiple social contexts influence students’ educational aspiration. In the field of social capital a neglected issue is how students obtain social capital from varying contexts and which contexts benefit them more to shape their future educational plan which consequently affects their level of aspiration. In this study, we aim to examine whether the students’ social capital, which is created by their families, has an extensive effect in shaping their educational aspiration compared to the social capital which is created in schools. We use the information collected from 553 students, their parents and 225 teachers from 12 selected secondary schools in Bangladesh. We conduct a series of multiple linear regression analyses to estimate the influence of family social capital and school social capital on the dependent variable of educational aspiration. To compare the effect size of family social capital and school social capital we consider the standardized Beta (β) weights of these two variables. The results show that beyond the socio-economic status, both family social capital and school social capital positively affect students’ educational aspiration. In addition, when we compare the effect size of these two variables, results show that family social capital has more strength compared to school social capital to predict the educational aspiration outcome of students.